Legacy and transformation: The enduring socioeconomic impact of Colonial railway infrastructure in contemporary Bogor - Syah, M Kautsar Thariq; Sa'adah, Putri Lailatus; Nurcahya, Yan; Suprianto, Sopian; Sufriadi, Dedi (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2025)
This study aims to historically examine the construction of the Bogor–Jakarta railway line during the Dutch colonial period between 1900 and 1930 and its impact on the socio-economic transformation of the local community. Utilizing a historical methodology encompassing heuristics, source criticism, interpretation, and historiography, the research draws on secondary literature and colonial archival records as its primary sources. The findings reveal that the railway's development was driven not only by economic interests in plantation logistics but also by military and administrative objectives to exert control over colonial territories. The railway functioned as a critical infrastructure for commodity export while also enhancing territorial connectivity, yet it simultaneously reinforced social disparities between the colonial elites and the indigenous population. The analysis demonstrates that, although the railway system improved the efficiency of people and goods mobility, it also operated as a tool of exclusion, discrimination, and centralized control. It accelerated regional economic growth but marginalized local participation in the developmental process. The study concludes that colonial infrastructure, such as the Bogor–Jakarta railway, represents an ambivalent legacy: it facilitated modernization while perpetuating inequality. This research contributes an interdisciplinary perspective that combines historical analysis with local economic development insights, offering a comprehensive understanding of how colonial transportation systems continue to influence mobility patterns and economic structures in the present day. It also provides a reflective basis for formulating transportation policies that are inclusive and historically informed. Contribution: By combining historical methodology with local economic development insights, the study offers a nuanced understanding of how colonial transportation infrastructure shaped socio-economic transformations and mobility patterns.